Track home maintenance business centers with GPS technology in the IR 4.0 era - Baker El-Ebiary Y.A.; Iryani Ahmad Saany S.; Aledinat L.S.; Ravindran Pathmanathan P.; Jusoh J.A.; Aseh K.; Mohamed R.R.; Nazari Mohd Rose A.; Moaiad Y.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Display devices; Maintenance; Ubiquitous computing; Display system; GPS technologies; High demand; Home-helpers; Local areas; Phone number; Global positioning system